Reformas al art. 629 del código del trabajo por vulnerar el derecho a impugnar la multa impuesta por el director regional del trabajo. - Illingworth Villa, Daniel Eduardo (2014)
This thesis is in its most practical sense, an analysis naturally focused in a very harsh reality that occurs within the scope of "REFORMS TO ART. 629 CODE OF WORK VIOLATE THE RIGHT TO DISPUTE THE FINE IMPOSED BY THE REGIONAL DIRECTOR OF WORK "". In this situation, it is necessary to verify and especially configure the legal security is important throughout the development process especially when it comes to bugs which legal duty appellees whether these administrative with this somehow giving due process and this prevent such violations and therefore thus avoid ambiguities and thereby provide certainty which is constitutionally enshrined. Thus my thesis research addresses this problem undoubtedly generating legal uncertainty, so it was necessary to present doctrinal, conceptual and legal references that allowed me to address the legal institution of labor law and analyze the Right to Work as a branch of law especially important in the society we live in, and that is taking autonomy in the future development of society and law. In the research I was useful criterion of the investigated population agreed with my view that it is necessary to reform the Labour Code incorporating and fulfilling what our constitution provides and thus avoid legal uncertainty and avoid the infringement of Article 629 of the Labour Code. In this context, this thesis is a reference invites us to reflect on Labor Law in Ecuador and studies necessary for the full development of society. My thesis then refers to the need for reform indicated and is based on theoretical and practical convenience of reform that I formulated my final conclusion of investigation.